(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2013)
On the flood plains meadows of the river Psel, that is used as pastures and haymakings, the features of productional process and growth of invasion species of Stenactis (Phalacroloma) annua (L) Cass. were studied. The analysis of reproduction of this species is conducted. The vitality structure of populations of Stenactis (Phalacroloma) annua (L) Cass. is established on pascual and fenisicial gradients.